Defective Early B Cell Tolerance Checkpoints in Patients With Systemic Sclerosis Allow the Production of Self Antigen–Specific Clones. Issue 2 (16th December 2021) - Glauzy, Salome; Olson, Brennan; May, Christopher K.; Parisi, Daniele; Massad, Christopher; Hansen, James E.; Ryu, Changwan; Herzog, Erica L.; Meffre, Eric
Abstract : Objective: Early selection steps preventing autoreactive naive B cell production are often impaired in patients with autoimmune diseases, but central and peripheral B cell tolerance checkpoints have not been assessed in patients with systemic sclerosis (SSc). This study was undertaken to characterize early B cell tolerance checkpoints in patients with SSc. Methods: Using an in vitro polymerase chain reaction–based approach that allows the expression of recombinant antibodies cloned from single B cells, we tested the reactivity of antibodies expressed by 212 CD19+CD21 low CD10+IgM high CD27− new emigrant/transitional B cells and 190 CD19+CD21+CD10−IgM+CD27− mature naive B cells from 10 patients with SSc. Results: Compared to serum from healthy donors, serum from patients with SSc displayed elevated proportions of polyreactive and antinuclear‐reactive new emigrant/transitional B cells that recognize topoisomerase I, suggesting that defective central B cell tolerance contributes to the production of serum autoantibodies characteristic of the disease. Frequencies of autoreactive mature naive B cells were also significantly increased in SSc patients compared to healthy donors, thus indicating that a peripheral B cell tolerance checkpoint may be impaired in SSc. Conclusion: Defective counterselection of developing autoreactive naive B cells in SSc leads to the production of self antigen–specific B cells that may secrete autoantibodies and allow the formation of immune complexes, which promote fibrosis in SSc.